Fonte ininterrupta de energia de dupla conversão com integração de energia fotovoltaica - Prado, Edemar de Oliveira (2024)
This work presents topologies and designs for the integration of photovoltaic systems with a double-conversion uninterruptible power supply (UPS). Based on the literature review, two topologies are derived and selected for evaluation and design. Topology 1 connects the photovoltaic system to the UPS DC bus without the use of interface converters, operating with a variable DC bus voltage. For designing Topology 1, a method is developed to select the suitable number of panels to be used in series, considering the panel model used, and the environmental mission profile. Additionally, an energy management algorithm is proposed to track the maximum power point of photovoltaic generation and ensure the hold-up time, introducing the concept of dynamic hold-up time. An application is developed for system design and return on investment evaluations, with the main metric being the return on investment over the federal funds rate. Topology 2 employs non-isolated DC-DC converters, boost, buck, or buck-boost, as interfaces between the photovoltaic system and the DC bus, operating with a constant DC bus voltage. The topology designs are evaluated considering component optimization techniques, with objectives of efficiency, cost, and volume. The design of each converter covers a range of panels in series for greater versatility. An application is developed for evaluating the return on investment over the federal funds rate. Among the evaluated converters, the boost converter exhibited a broader operating range compared to the buck and buck-boost converters, making it preferable for use in the studied UPS. Using a string of panels, Topology 1 presented the best return on investment. The return on investment over the federal funds rate with a boost converter with 11 and 12 panels in series and with a buck converter across the entire evaluated range is similar to the return on investment over the federal funds rate obtained with Topology 1, resulting in returns on investment 60% higher than the federal funds rate. The return on investment over the federal funds rate using a buck-boost converter is on average 14.31% lower compared to Topology 1.